Comparing the quality characteristics and bacterial communities in meatballs with or without blown pack spoilage. (August 2020) - Li, Ran; Cai, Linlin; Gao, Tingxuan; Li, Chunbao; Zhou, Guanghong; Ye, Keping
Abstract: Differences of the quality characteristics and bacterial communities in meat products with or without blown pack spoilage (BPS) were not well illustrated. The objectives of this study were to investigate the quality characteristics and bacteria of meatballs with or without BPS, to explain the possible cause of meat products with BPS. The results revealed a 12.5% BPS ratio with meatballs and the pack volumes in the BPS samples were nearly two-fold larger than those of the normal samples after storage for 28 days. Compared with the normal group, the meatballs in the BPS group had a higher CO2 abundance (78.53%) and a lower pH (5.09). Besides, the relative concentrations of some spoilage-related compounds (such as acetic acid) were significantly higher in BPS meatballs (P < 0.05). Principal component analysis provided evidence of clear differences in the bacterial communities between the BPS and normal groups. Pseudomonas (30.46%), Enterobacter (20.76%), Pantoea (13.38%), Serratia (12.63%), and Rahnella (10.15%) were dominant in the BPS group, whereas Pseudomonas (42.51%), Carnobacterium (18.74%), Pantoea (17.56%), and Enterobacter (14.80%) were dominant in the normal group. The findings of this study may provide a theoretical basis for understanding potential mechanisms underlying BPS. Highlights: The BPS rate was 12.5% and the pack volumes increased ~2-fold after 4 weeks. The CO2 level (78.53%) in blown packs decreased the pH (5.09) in BPS meat balls. Gas-forming bacteria affected the VOCs and bacterial communities of meatballs. Some spoilage-related compounds were significantly more abundant in BPS meatballs. The predominant genera in the BPS and normal meatball groups were identified.